Evaluación del uso de la microalga Chlorella Vulgaris en la remoción de materia orgánica de las aguas residuales de la PTAR el Salitre a nivel laboratorio (2017)
The objective of this research project is to evaluate the use of the microalgae Chlorella vulgaris in the removal of organic matter from the wastewater treated by the El Salitre PTAR; with emphasis on the removal by chemical oxygen demand (COD) and total suspended solids (SST), which are the parameters on which the Salitre PTAR is based to evaluate the removal of organic matter in its process. The incidence of microalgae Chlorella vulgaris was evaluated in other physicochemical parameters such as: Total Solids (ST), Volatile Solids (SV), Volatile Suspended Solids (SSV), and pH, Turbidity, Alkalinity and Conductivity.